The Role of The Community Around The Buffer Village of Alas Purwo National Park in Conservation Based on Local Wisdom - Sukesi, Keppi; Hidayat, Kliwon; Yuliati, Yayuk (Universitas Negeri Semarang, 2021)
This research describes the life of the local community of Alas Purwo National Park buffer village, especially Kalipait Village which has local wisdom in the form of a number of traditions, rules or restrictions that are still valid for generations. This local wisdom has the value of ecological intelligence about the activity of human relationships with its ecosystems. Local wisdom as a reference in the management of forest areas and coastal waters, both in the form of myths and abstinence. The center of attention of ecological studies according to Julian Steward is the process of cultural adaptation to the environment and the ecological process has reciprocal laws. The type of research used is descriptive qualitative with case study design. The results showed that the community around Alas Purwo National Park has local wisdom in the form of a number of traditions, rules or restrictions that are still valid for generations which are then maintained and obeyed until now. Both influence each other that the environment has an influence over human culture and behavior. The abstinence is in the form of a ban on killing peacocks and abstinence in the payang system.Â Â Â